Vaginal bleeding in prepubertal girls-a case series in Malaysia - NS, Omar; AA, Zainuddin; A, Anizah; AI, Nurkhairulnisa; L, Sivapatham; AW, Ana Vetriana; AG, Nur Azurah (Penerbit Universiti Kebangsaan Malaysia, 2023)
The etiology of prepubertal vaginal bleeding varies from isolated pubertal causes to malignant tumors and generates significant anxiety among girls and their caretakers. Hence, these cases require careful assessment and management. This is a report of five cases of prepubertal vaginal bleeding with various causes and were managed in a tertiary referral center in Malaysia. The first case was a 6-year-old girl who had no pubertal changes with 3 weeks’ history of bleeding. She underwent examination under anesthesia and found to have multiple vaginal polyps. Another 6-year-old girl noted to have a doughnut-shaped mass protruding from her urethral meatus. She was treated with estrogen cream and sitz baths. Another child had early breast development while pelvic ultrasound revealed a multiseptated ovarian cyst requiring a cystectomy. A 19-month-old toddler had a large intravaginal mass. She required further investigation, referral to the pediatric surgeon and oncologist for treatment of a malignant yolk sac tumor. Lastly, an 8-year-old girl was noted to have monthly vaginal spotting without any secondary sexual characteristics development. Prepubertal vaginal bleeding is abnormal thus requires prompt assessment to ascertain the cause and administer appropriate management. It is important to rule out sexual abuse and malignancy. Examination under anaesthesia and vaginoscopy is recommended when imaging modality is inconclusive. Referral to tertiary centres experienced in managing such cases ensures good outcomes. Thorough targeted history-taking and pediatric-specific gynecological examination skills are crucial to formulate accurate diagnosis and appropriate management.